Implementasi Kebijakan Pendelegasian Wewenang Urusan Kepegawaian di Dinas Pekerjaan Umum Bina Marga dan Tata Ruang Provinsi Sumatera Selatan - Sulastri, Sri; Zuber, Konar; Ariyati, Desi (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2022)
Delegation of authority is one aspect of the organization that is very important as well as at the Department of Public Works of Highways and Spatial Planning of South Sumatra Province, because delegation will accelerate and expedite the implementation of work, by itself will avoid delays in the implementation of work. All organizations have a common goal. to be achieved and must be clearly formulated, in the implementation of the organization's goals it is poured into the main task. The problems that have been identified in the preliminary study conducted by researchers that must be considered regarding the Delegation of Authority at the Public Works Department of Highways and Spatial Planning of South Sumatra Province are interesting to study, namely: 1). The existence of employees who carry out tasks not based on existing levels, among others, it is seen that there are employees who take care of administration directly to the leadership not through the General and Personnel Sub-Sector. 2) There is still distrust of the leadership in delegating authority to subordinates, in this case the leadership still interferes in the implementation of the work, which causes employees to feel distrusted and do not carry out the work that was previously submitted to them. This study uses a qualitative approach, which is a research procedure that aims to describe certain circumstances, which are described in separate words or sentences to obtain conclusions. The focus of the research in this study is the implementation of the policy of delegation of authority at the Public Works Department of Highways and Spatial Planning of the Province of South Sumatra. The data analysis technique used is qualitative data analysis techniques, while the data collection techniques used are observation, interviews and documentation.The conclusion of this study is that based on indicators of information transmission, information clarity and consistency of information have gone well, the delivery of information to be provided by the wider community has been structured in relation to government policies and programs in providing information consistently.